Frequency of Parafunctional Habits and Malocclusion in Patients with Temporomandibular Disorders in Public Dental Hospital - Bukhari, Syed Junaid Hussain; Khan, Shafi Ullah; Babar, Adnan; Somair, Sana; Rehman, Anis Ur; Imran, Ayesha (Pakistan Armed Forces Medical Journal, 2025)
Objective: To correlate the frequency of parafunctional habits and dental malocclusion in patients presenting with and without temporomandibular joint disorders.Study Design: Correlational study.Place and Duration of Study: Department of Oral and Maxillofacial Surgery, Armed Forces Institute of Dentistry, Rawalpindi, Pakistan, from Feb to Jul 2024.Methodology: A total of 150 patients with parafunctional habits and dental malocclusion issues were assessed for presence or absence of temporomandibular joint (TMJ) disorders. The assessment for presence or absence of TMJ disorders was done according to standard guidelines furnished by the American Academy of Orofacial Pain, which included TMJ pain, muscle stiffness, and joint noises. Primary variables studied were the frequency of parafunctional habits and malocclusion between patients with and without TMJ disorders.Results:  Bruxism was reported in 47(51.1%) versus 12(20.7%) patients (p